Activity of TAS4464, a novel NEDD8 activating enzyme E1 inhibitor, against multiple myeloma via inactivation of nuclear factor κB pathways. Issue 12 (23rd October 2019) - Muraoka, Hiromi; Yoshimura, Chihoko; Kawabata, Rumi; Tsuji, Shingo; Hashimoto, Akihiro; Ochiiwa, Hiroaki; Nakagawa, Fumio; Fujioka, Yayoi; Matsuo, Kenichi; Ohkubo, Shuichi
Abstract: The ubiquitin proteasome pathway is essential for the proliferation and survival of multiple myeloma (MM) cells. TAS4464, a novel highly potent inhibitor of NEDD8 activating enzyme, selectively inactivates cullin‐RING ubiquitin E3 ligases, resulting in accumulation of their substrates. Here, we examined 14 MM cell lines treated with TAS4464. TAS4464 induced growth arrest and cell death in the MM cell lines even in the presence of bone marrow stromal cells. It also induced the accumulation of phospho‐inhibitor of κBα and phospho‐p100, impaired the activities of nuclear factor κB (NF‐κB) transcription factors p65 and RelB, and decreased the expression of NF‐κB target genes, suggesting that TAS4464 inhibits both the canonical and non–canonical NF‐κB pathways. TAS4464 had similar effects in an in vivo human‐MM xenograft mouse model in which it was also observed to have strong antitumor effects. TAS4464 synergistically enhanced the antitumor activities of the standard MM chemotherapies bortezomib, lenalidomide/dexamethasone, daratumumab and elotuzumab. Together, these results suggest that the anti–MM activity of TAS4464 occurs via inhibition of the NF‐κB pathways, and that treatment with TAS4464 is a potential approach for treating MM by single and combination therapies. Abstract : In this study, we showed antitumor activity and molecular insight into the mechanism of action of TAS4464, an NEDD8‐activating enzyme inhibitor, in multiple myeloma (MM) cells. TAS4464 led to strong antitumor activity through inactivation of NF‐κB signaling activated in MM cells. This study suggests that treatment with TAS4464 is a potential approach for treating MM.